Evaluation of Iranian Chemical Industries - Hassanpour, Malek (International Journal of Chemistry and Materials Research, 2020)
The chemical industry is part of the industries, which supply the chemicals needed by other industries through the conversion of raw materials into the required products. The current cluster study of Iranian Chemical Industries (ICI) encompassed all input and output materials streams, ICI energy demands and technologies applied based on the assessment carried out by both Iranian Industries Organization (IIO) and Iranian Environment Protection Agency (IEPA). Then the raw data were empirically evaluated via traditional to novel decision-making models, SPSS software and Excel 2013 to make a decision about the classification of ICI and pave the way for further industrial ecology studies in a certain cluster as the objective of current research. T-test analysis had presented no significant difference among the main criteria of ICI such as the number of staff, power, water, and fuel demands and the land area occupied by ICI individually. Finally, the obtained values in the weighing and ranking systems and Data Envelopment Analysis (DEA) was composed to classify ICI as a cluster ranking and prioritized them from the highest weighting value and efficiency score to the lowest one based on the main criteria and an inventory of availability.